Didactic poetry as cultural preservation in the anthology Ratapan Laut Sawu by NTT poets - Imelda Oliva Wissang (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
Poetry as a literary work functions not only as an aesthetic expression, but also as a medium for conveying cultural values ​​and education. However, in academic practice and literary studies, poetry is often understood solely in linguistic terms, leaving its didactic and cultural functions unexplored. This study aims to describe in depth the form, meaning, and function of didactic poetry in preserving cultural heritage, as presented in the anthology "Lamentations of the Sawu Sea" by poets from East Nusa Tenggara (NTT). This study uses a qualitative approach with a descriptive-narrative method. The research data consists of poetry texts in the anthology "Lamentations of the Sawu Sea", which are strengthened by data from interviews, observations, and documentation related to the use of poetry in educational and cultural contexts. Data collection was conducted through reading and note-taking, while data analysis employed an interactive model that included data reduction, data presentation, and conclusion. The results of the study indicate that the poems in the anthology are didactic, employing symbols, imagery, and narratives of collective experiences that convey religious values, ecological wisdom, traditional traditions, local food, and love for one's hometown. The didactic poetry in this anthology serves as a means of cultural preservation, working on aesthetic, cultural, and pedagogical levels. The research concludes that "Lamentations of the Sawu Sea" makes a significant contribution to cultural education and to strengthening the local identity of the NTT community through literature.